Study on Vibrational Power Flow Propagation Characteristics in a Laminated Composite Cylindrical Shell Filled with Fluid - Jingxi Liu; Wentao He; De Xie (Shock and Vibration)
The characteristics of vibrational power flow in an infinite laminated composite cylindrical shell filled with fluid excited by a circumferential line cosine harmonic force are investigated using wave propagation approach. The harmonic motions of the shell and the fluid filled in the shell are described by Love shell theory and acoustic wave equation, respectively. Under the driving force, the vibrational power flow input into the coupled system and the transmission of the power flow carried by different internal forces (moments) of the shell in the axial direction are established. Numerical computations are implemented to investigate the vibrational power flow input and its propagation. It is found that characteristics of the vibrational power flow vary with different circumferential mode orders and frequencies, and the presence of fluid in the shell significantly affects the vibration of the shell structure. Additionally, parametric investigations are carried out to study the effects of the fiber orientation, modulus ratio E11/E22, and thickness-to-radius parameter h/R on input power into the coupled system and propagation power along the shell axial direction. This work will provide some guidance for the vibration control of the laminated composite cylindrical shell.